MUTU KIMIA PADA KALDU BUBUK NABATI BERBAHAN BAKU JAMUR MERANG (VOLVARIELLA VOLVACEA) DAN WORTEL (DAUCUS CAROTA L.) - AFE DWIANI; SUBURI RAHMAN; SITI AMINAH (GANEC SWARA, 2024)
Mushroom-based flavoring is one of the vegetable source food additives that contain glutamate so that it can be used as a substitute for artificial flavoring. Mushrooms that can be used are straw mushrooms. The addition of carrots aims to add nutrients to vegetable stock powder products. This aims of this study was to determine the combination of straw mushroom and carrot on chemical quality and the best treatment produced by vegetable stock  powder. This research is an experimental research conducted in the laboratory. The first thing that was done was making vegetable stock powder with combination of straw mushroom and carrot then continued with chemical analysis. The results showed that the best treatment for the powdered stock of straw mushroom and carrot based on the chemical quality in this study was treatment J1 (100% merang mushroom: 0% carrot) with a value of 11.32% moisture content, 9.20% ash content and 12.63% crude fiber.